Evolutionary Insight into the Association between New Jersey Polyomavirus and Humans - Aref-Abdolllah Aghebatrafat; Chris Lauber; Kevin Merkel; Barbara Fruth; Kevin Langergraber; Martha M. Robbins; Roman M. Wittig; Fabian H. Leendertz; Sébastien Calvignac-Spencer (Viruses, 2023)
Advances in viral discovery techniques have led to the identification of numerous novel viruses in human samples. However, the low prevalence of certain viruses in humans raises doubts about their association with our species. To ascertain the authenticity of a virus as a genuine human-infecting agent, it can be useful to investigate the diversification of its lineage within hominines, the group encompassing humans and African great apes. Building upon this rationale, we examined the case of the New Jersey polyomavirus (NJPyV; Alphapolyomavirus terdecihominis), which has only been detected in a single patient thus far. In this study, we obtained and analyzed sequences from closely related viruses infecting all African great ape species. We show that NJPyV nests within the diversity of these viruses and that its lineage placement is compatible with an ancient origin in humans, despite its apparent rarity in human populations.